2013
DOI: 10.1080/09540121.2013.772279
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviour after antiretroviral therapy initiation in female sex workers and HIV-positive patients from the general population, Cotonou, Benin

Abstract: From September 2008 to December 2011, we enrolled and followed-up 247 HIV-negative, 88 untreated and 32 treated HIV-positive female sex workers (FSWs), as well as 238 untreated and 115 treated HIV-positive patients from the general population (GP) of Cotonou, Benin. We wanted to assess the effect of antiretroviral therapy (ART) on sexual risk-taking in FSWs and patients from the GP. We used multivariate log binomial regression models for repeated measures to compare risky behaviours reported during pre-ART and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
1
9
1
Order By: Relevance
“…Also, there are speculations that initiation of antiretroviral treatment promotes risky sexual behaviour in HIV positive persons 26 . The evidence is not consistent given the different findings from diverse contexts 27,28 .…”
Section: Sexual Behaviour Among Other Groupscontrasting
confidence: 44%
“…Also, there are speculations that initiation of antiretroviral treatment promotes risky sexual behaviour in HIV positive persons 26 . The evidence is not consistent given the different findings from diverse contexts 27,28 .…”
Section: Sexual Behaviour Among Other Groupscontrasting
confidence: 44%
“…Overall, our search showed that six articles examined ART initiation (Braunstein et al, 2011; Diabaté et al, 2011; Konate et al, 2011; Cowan et al, 2013; Diabaté et al, 2013; Mtetwa, Busza, Chidiya, Mungofa, & Cowan, 2013). Five of the articles used quantitative methods to assess determinants of ART initiation, while one article used qualitative methods to provide a more in-depth understanding of care experiences related to ART initiation among FSW in Zimbabwe (Mtetwa et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…74 However, studies of African FSWs have shown that sexual risk taking in women on ART can be minimized if behavioral change programs are maintained. [75][76][77] Even when assuming a more conservative efficacy of ART in reducing HIV infectivity, targeting ART towards FSW still prevents more infections than the current policy. Although targeting OSW reduces efficiency due to their lower PAF, it is likely that their inclusion would be easier to implement.…”
Section: Discussionmentioning
confidence: 99%